An investigation of the effects of step drill geometry on drilling induced delamination and burr of Ti/CFRP stacks. (1st March 2020) - Jia, Zhen-yuan; Zhang, Chong; Wang, Fu-ji; Fu, Rao; Chen, Chen
Abstract: The Ti/CFRP stacks are widely used in the field of aerospace since their excellent properties. However, it is quite a challenge work to obtain quality holes in one-shot drilling due to the tremendous differences in material properties of Ti and CFRP. In this paper, a novel step drill structure which could reduce the delamination and burr by controlling step diameters ratio is proposed. Considering the geometric structure of step drill and the properties of the materials, the cutting loads prediction model and three simplified drill-exit damage model are established in order for confirming critical condition of the defect. Consequently, the relationship between the burr height, delamination length and the diameter of step-drill bit are clarified. Then a novel step drill with variation step ratio is designed. And geometrical analysis proved that it could effectively improve the quality of drill-exit. In addition, comparative experiments were carried out, the result showed that the proposed step drill structure can effectively reduce the damages such as the burr and delamination as expected.